Single-layer seromuscular Continuous Versus Two-Layers Intestinal Anastomosis Of Small bowel in Baghdad Teaching Hospital (A prospective Study) - Habash, Mohammed M.; Hammoudi, Yahya K.; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Anastomosis may be done with the help of stapling devices, by using double layered suturing technique or by a single layer technique.Patients and methods: A prospective study conducted in Baghdad Teaching Hospital, Iraq.  A total of sixty- four patients were included in this study. They were divided into two groups; group A, 28 patients, single layer seromuscular continuous anastomosis was done and group B, 36 patients underwent conventional double layered anastomosis.Objective: The aim of the study is to prove that a single layer continuous technique can be constructed in a significantly less time with similar rate of complications compared with two layers technique.Results: There were, 15 male (53.6%) and 13 (46.4%) female within group A and 20 (55.6%) male and 16 (44.4%) female within the group B. There was no significant difference in gender distribution or mean age between or within groups. Bullet and sharp nail injuries to the abdomen were the most common causative agents followed by malignant disease of GIT. Wound infection was the most frequent complication in both groups as fourteen patient out of 64 (21.9%) developed wound infection; 8 of them were among group B.  There was no significant difference in the incidence of anastomotic leakage; in group A was 3.6%, while in group B was 4.7%. The average time for the construction of the single layer anastomosis was 20 min and in double layer it was 35 min. The difference in average time is statistically significantConclusion: The single-layer continuous anastomosis requires less time to construct and has a similar risk of leakage compared with the two-layer technique. It also costs less than any other method and can be safely introduced into a surgical training program.